SOSIALISASI PENGGUNAAN BPJS DI ASRAMA STIKES SANTA ELISABETH MEDAN - Pomarida Simbolon; Nagoklan Simbolon; Adrian Hutauruk; Anthonyus Anthonyus (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
The National Health Insurance (JKN) is a program of the National Social Security System (SJSN) organized by the Health Social Security Administration Agency (BPJS) and came into effect on January 1, 2014. The growth prevalence of JKN participants has reached 241.7 million people as of June 30 2022. The purpose of this community service is to provide insight to the public regarding the use of BPJS in the STIKes Santa Elisabeth Medan dormitory. Where after conducting field visits to identify knowledge on using BPJS, many still do not know how to use BPJS. Giving questionnaires that were carried out before and after the socialization activities, students of the Health Information Management study program at the STIKes Santa Elisabeth Medan dormitory experienced an increase in knowledge after the post-test was carried out by 61.14%.